Before you study this concept, you are adviced to read:
What is Ratio ?
What is Percentage ?
What are Terms of Ratio ?
How to Convert Fraction to Percentage ?
Steps of converting Ration to Percentage are as follows:
1) Calculate Sum of terms of given ratio
2) Represent respective Term of Ratio in Fractional form
3) Convert Fractional Form into percentage
Example 1: Convert Ratio 4 : 1 into percentage.
Solution: Terms of given ratio are:
First Term = 4
Second Term = 1
Steps of Conversion are as follows:
Step 1 : Calculate Sum of terms of given ratio and we get:
4 + 1 = 5
Therefore sum of terms of given ratio = 5
Step 2 : Represent respective Term of Ratio in Fractional form
Fractional Form of First Term = First Term / Sum of terms
Put value of first term and sum of terms from above and we get:
= 4/5
Therefore, Fractional Form of First Term = 4/5
Fractional Form of Second Term = Second Term / Sum of terms
Put value of second term and sum of terms from above and we get:
= 1/5
Therefore, Fractional Form of Second Term = 1/5
Step 3 : Convert Fractional Form into percentage
Percentage of First Term = Fractional Form of First Term x 100 %
Put value of Fractional Form of First Term from above and we get:
= (4/5) X 100
Solve the above expression and we get:
= 80
Therefore, Percentage of First Term = 80%
Percentage of Second Term = Fractional Form of Second Term x 100 %
Put value of Fractional Form of Second Term from above and we get:
= (1/5) X 100
Solve the above expression and we get:
= 20
Therefore, Percentage of Second Term = 20%
Hence, 4 : 1 = 80% : 20%
Example 2: Express Ratio 4 : 6 into percentage form.
Solution: Terms of given ratio are:
First Term = 4
Second Term = 6
Steps of Conversion are as follows:
Step 1 : Calculate Sum of terms of given ratio and we get:
4 + 6 = 10
Therefore sum of terms of given ratio = 10
Step 2 : Represent respective Term of Ratio in Fractional form
Fractional Form of First Term = First Term / Sum of terms
Put value of first term and sum of terms from above and we get:
= 4/10
Therefore, Fractional Form of First Term = 4/10
Fractional Form of Second Term = Second Term / Sum of terms
Put value of second term and sum of terms from above and we get:
= 6/10
Therefore, Fractional Form of Second Term = 6/10
Step 3: Convert Fractional Form into percentage
Percentage of First Term = Fractional Form of First Term x 100 %
Put value of Fractional Form of First Term from above and we get:
= (4/10) X 100
Solve the above expression and we get:
= 40
Therefore, Percentage of First Term = 40%
Percentage of Second Term = Fractional Form of Second Term x 100 %
Put value of Fractional Form of Second Term from above and we get:
= (6/10) X 100
Solve the above expression and we get:
= 60
Therefore, Percentage of Second Term = 60%
Hence, 4 : 6 = 40% : 60%
 Study More Solved Questions / Examples
